2017
DOI: 10.1136/ejhpharm-2017-001295
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder opinions on value in healthcare

Abstract: ObjectivesTo determine how the value of new medicines is defined from the perspective of different stakeholders in nine European countries.MethodsWe carried out an explorative survey by conducting in-depth qualitative interviews with a range of experts with health technology assessment, clinical provision, health economics, payer, academic and industry experience. Experts were asked to distribute 100 points over a predefined list of attributes related to value. In total, 30 interviews were conducted with seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Similarly, opinions from multiple stakeholders should also be considered during drug value assessments. [52] Among these, the patients’ voice and the opinion of the patient group should be given more consideration than is typically the case. [53] Based on the research results, regardless of whether or not the opinions of the patient group or the industry on weights were considered, the final research results remained unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, opinions from multiple stakeholders should also be considered during drug value assessments. [52] Among these, the patients’ voice and the opinion of the patient group should be given more consideration than is typically the case. [53] Based on the research results, regardless of whether or not the opinions of the patient group or the industry on weights were considered, the final research results remained unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study had some limitations mainly due to the inherent nature of the study focused only in a P&TC setting. Recent studies have suggested that, in healthcare decision making, the stakeholders would give different values to different criteria and that values assigned in drug evaluation are subjective and depending on their objectives and their points of view (24). In this context, it has been reported that when evaluating the contribution of a new medical device the relative importance of the criteria framework was in accordance with points of view of evaluators and their objectives (25).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the therapy on life expectancy and quality of life, the cost of the new therapy, and the burden on the system of integrating a new drug are among the factors that are considered when a government decides if it will pay for a new therapy [71]. Stakeholders differ in their perspectives of what constitutes value [72][73][74][75]. Patients, their loved ones, and their physicians want access to therapies that improve cancer symptoms, prolong life, and offer hope.…”
Section: Controlling Drug Pricesmentioning
confidence: 99%